Development of optimised tissue-equivalent materials for proton therapy. (7th April 2023) - Cook, H; Simard, M; Niemann, N; Gillies, C; Osborne, M; Hussein, M; Rompokos, V; Bouchard, H; Royle, G; Pettingell, J; Palmans, H; Lourenço, A
Abstract: Objective . In proton therapy there is a need for proton optimised tissue-equivalent materials as existing phantom materials can produce large uncertainties in the determination of absorbed dose and range measurements. The aim of this work is to develop and characterise optimised tissue-equivalent materials for proton therapy. Approach . A mathematical model was developed to enable the formulation of epoxy-resin based tissue-equivalent materials that are optimised for all relevant interactions of protons with matter, as well as photon interactions, which play a role in the acquisition of CT numbers. This model developed formulations for vertebra bone- and skeletal muscle-equivalent plastic materials. The tissue equivalence of these new materials and commercial bone- and muscle-equivalent plastic materials were theoretical compared against biological tissue compositions. The new materials were manufactured and characterised by their mass density, relative stopping power (RSP) measurements, and CT scans to evaluate their tissue-equivalence. Main results . Results showed that existing tissue-equivalent materials can produce large uncertainties in proton therapy dosimetry. In particular commercial bone materials showed to have a relative difference up to 8% for range. On the contrary, the best optimised formulations were shown to mimic their target human tissues within 1%–2% for the mass density and RSP. Furthermore, their CT-predicted RSP agreed within 1%–2% of the experimental RSP, confirming their suitability as clinical phantom materials. Significance . We have developed a tool for the formulation of tissue-equivalent materials optimised for proton dosimetry. Our model has enabled the development of proton optimised tissue-equivalent materials which perform better than existing tissue-equivalent materials. These new materials will enable the advancement of clinical proton phantoms for accurate proton dosimetry.